ALL HANDS ON DECK. - LITTLE, JASON (Public Management (00333611), 2020)
The article focuses on the navigation of Texas in Utility Billing Crisis. It focuses on the role of Software as a Service (or SaaS) platform to minimize the need for the organization to provide additional hardware, any software, technicians, or data security for critical business function; and also highlights the contract of community, Melissa with FATHOM for a full-service advanced metering infrastructure (AMI) utility billing platform.